Varro and the Two-Headed City - López Barja de Quiroga, Pedro (Gerión. Revista de Historia Antigua, 2024)
An in-depth analysis of Varro’s sentence (quoted by Nonius) on Gracchus judiciary law having created a two-headed city shows how the polygrapher artfully combined Plato’s political considerations on constitutional change with Roman priestly lore (haruspicina). Varro’s sympathies for the optimates find in this sentence its best expression. Posidonius may have been an intermediate stage in the use of these Platonic ideas to understand Roman political history.